2009
DOI: 10.1172/jci35298c1
|View full text |Cite
|
Sign up to set email alerts
|

The FGF system has a key role in regulating vascular integrity

Abstract: During the preparation of the manuscript, different fields of the same sample for WGA immunofluorescence staining were mistakenly used to represent 2 distinct treatment groups on 2 occasions, in Figures 2 and 7, and some of the raw data for the earlier experiments were lost due to poor record keeping. All authors have agreed to retract the article. The authors sincerely apologize for any inconvenience this action has caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 0 publications
4
93
0
Order By: Relevance
“…Quantitative RT-PCR demonstrated expression of Fgfr3 (but not Fgfr4) in lung ECs but did not detect significant changes in the expression of these genes in ECs isolated from DFF and DCKO adult lung. Notably, and in agreement with previous findings (43,44), we observed a modest, but statistically significant, increase in vascular permeability in response to an acute inflammatory stimulus, suggesting a nonhomeostatic role for EC FGF signaling in the maintenance of vascular barrier function. However, other vascular functions, including BP and vascular reactivity, were not dependent on EC and hematopoietic cell FGFR1/2 signaling.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Quantitative RT-PCR demonstrated expression of Fgfr3 (but not Fgfr4) in lung ECs but did not detect significant changes in the expression of these genes in ECs isolated from DFF and DCKO adult lung. Notably, and in agreement with previous findings (43,44), we observed a modest, but statistically significant, increase in vascular permeability in response to an acute inflammatory stimulus, suggesting a nonhomeostatic role for EC FGF signaling in the maintenance of vascular barrier function. However, other vascular functions, including BP and vascular reactivity, were not dependent on EC and hematopoietic cell FGFR1/2 signaling.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the results published by Murakami et al (43) and Murakami and Sakurai (44), mice lacking EC FGFR1/2 actually maintained normal basal barrier functions in the skin and retinal vascular beds, even on a sensitized (Vegfr2 haploinsufficient) genetic background. Explanations for these differences include effects of acute (43,44) vs. chronic (this study) pathway inhibition, and the targeting of multiple vascular cell types (43,44) vs. only EC and hematopoietic cells (this study). Additionally, Fgfr1/2 gene inactivation could be incomplete or could be compensated for by increased expression of FGFR3 or FGFR4, which could explain in part the lack of a developmental phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…4A). The role of KGF is intriguing given the previous studies of ALI in animal models and a recent study by Murakami et al (45) who reported that fibroblast growth factors (FGF) are key mediators responsible for the maintenance of endothelial barrier homeostasis. In addition, in this model, the impact of MSCs on paracellular permeability cannot be separated out from its impact on transcellular ion and fluid transport on AFC measurements.…”
Section: Discussionmentioning
confidence: 99%
“…How endothelial cell keep quiescence in the presence of FGF is less understood. On the one hand, physiological FGF signaling is necessary for the maintenance of vascular integrity [83] and, on the other hand, FGF induces angiogenesis [84]. Although cell confluence inhibits FGF induced p42/p44 MAPK (ERK1/2) activity in mouse vascular endothelial cells, it remains elusive whether VE-cadherins or other cell-cell contact molecules participate in this process [5].…”
Section: Contact Inhibition and Mitogenic Quiescencementioning
confidence: 99%
“…Although FGF signaling has been identified as a strong pro-angiogenic factor in physiological [84] and pathological situations [192], Murakami et al [83] have demonstrated that it also plays a key role in the maintenance of vascular integrity, because a loss of FGF results in severe impairment of the endothelial barrier function and eventually to a disintegration of the vasculature. Thus, it would not be favorable for endothelial cells to just block FGF signaling at confluence.…”
Section: Spry2 Expression Controls Monolayer Integrity and Quiescencementioning
confidence: 99%